The Role of Firm Dynamics in the Green Transition: Carbon Productivity Decomposition in Finnish Manufacturing - Natalia Kuosmanen; Terhi Maczulskij (Institute of Labor Economics (IZA), 2023)
This paper explores the importance of firm dynamics, including entry and exit and the allocation of carbon emissions across firms, on the green transition. Using the 2000–2019 firm-level register data on greenhouse gas emissions matched with the Financial Statement data in the Finnish manufacturing sector, we examine the sources of carbon-productivity growth and assess the relative contributions of structural change and firm dynamics. We find that continuing firms were the main drivers of carbon productivity growth whereas the contribution of entering and exiting firms was negative. In addition, the allocation of emissions across firms appeared to be inefficient, with a negative impact on carbon productivity growth over the study period. Our analysis also revealed a positive relationship between labor-intensive firms and carbon productivity, but firms with a larger market share tended to be less productive in terms of carbon use.
Keywords: D24; L60; Q54; 330; carbon productivity; decomposition analysis; firm dynamics; firm-level data; manufacturing sector